Fringe 2013 7th International Workshop on Advanced Optical Imaging and Metrology - Osten, Wolfgang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
In continuation of the FRINGE Workshop Series this Proceeding contains all contributions presented at the 7. International Workshop on Advanced Optical Imaging and Metrology. The FRINGE Workshop Series is dedicated to the presentation, discussion and dissemination of recent results in Optical Imaging and Metrology. Topics of particular interest for the 7. Workshop are: - New methods and tools for the generation, acquisition, processing, and evaluation of data in Optical Imaging and Metrology (digital wavefront engineering, computational imaging, model-based reconstruction, compressed sensing, inverse problems solution) - Application-driven technologies in Optical Imaging and Metrology (high-resolution, adaptive, active, robust, reliable, flexible, in-line, real-time) - High-dynamic range solutions in Optical Imaging and Metrology (from macro to nano) - Hybrid technologies in Optical Imaging and Metrology (hybrid optics, sensor and data fusion, model-based solutions, multimodality) - New optical sensors, imaging and measurement systems (integrated, miniaturized, in-line, real-time, traceable, remote) Special emphasis is put on new strategies, taking into account the active combination of physical modeling, computer aided simulation and experimental data acquisition. In particular attention is directed towards new approaches for the extension of existing resolution limits that open the gates to wide-scale metrology, ranging from macro to nano, by considering dynamic changes and using advanced optical imaging and sensor systems.
New methods and tools for the generation, acquisition, processing, and evaluation of data in Optical Imaging and Metrology -- Application-driven technologies in Optical Imaging and Metrology -- High-dynamic range solutions in Optical Imaging and Metrology -- Hybrid technologies in Optical Imaging and Metrology -- New optical sensors, imaging and measurement systems.
Keywords: Engineering; Computer vision; System safety; Engineering; Quality Control, Reliability, Safety and Risk; Optics, Optoelectronics, Plasmonics and Optical Devices; Signal, Image and Speech Processing; Image Processing and Computer Vision